2003
DOI: 10.1002/jsfa.1513
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oil‐in‐water emulsion characteristics on initial dynamic flavour release

Abstract: Properties of oil-in-water (O/W) emulsions affecting initial dynamic flavour release were studied in real time considering mouth conditions. Aroma molecules from different chemical classes at concentrations typically present in beverages were used. The emulsion droplet diameter showed no significant influence on the dynamic flavour release. No barrier properties of the emulsifier were found, as the flavour release from equilibrated emulsions flavoured via either the oil phase or the aqueous phase showed no sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
37
0
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 34 publications
5
37
0
4
Order By: Relevance
“…In accordance with recent results (4,13,17), flavor release correlated linearly with time (average R 2 = 0.992) under the conditions applied for experimentation. Even though foodlike flavor concentrations were applied, mean CV in the range of 4.2 to 15.1%, with an average of 8.6%, showed the reproducibility of the apparatus used (cf.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…In accordance with recent results (4,13,17), flavor release correlated linearly with time (average R 2 = 0.992) under the conditions applied for experimentation. Even though foodlike flavor concentrations were applied, mean CV in the range of 4.2 to 15.1%, with an average of 8.6%, showed the reproducibility of the apparatus used (cf.…”
Section: Resultssupporting
confidence: 90%
“…Land (1) found the distribution of a lipid in an aqueous phase to affect flavor release. However, more recently several studies have shown the opposite, that is, flavor release is independent of the interfacial area between the oil and the water phases (2)(3)(4). Nonionic emulsifiers, such as Tweens, or surfactants based on MAG and DAG did not serve as barriers at the oil interface nor as solubilizers in terms of micelles (4)(5)(6).…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…It has been reported that lipids influence flavour perception in terms of both aroma release and textural changes (Daget et al, 1987;Malone and Appelqvist, 2003). As a result, the reformulation of flavours consisting of foods with reduced fat requires considerable work so that they can meet the needs and expectations of consumers (Rabe et al, 2003). Considering these aspects, the lipids present in the Brazil nut have enormous potential for the formulation of mayonnaisetype emulsions, in addition to having good nutritional characteristics.…”
Section: Introductionmentioning
confidence: 99%